2015
DOI: 10.1371/journal.pone.0117359
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Six-Minute Walking Performance with Quality of Life is Domain- and Gender-Specific in Healthy Older Adults

Abstract: We analyzed the relationship between performance on the 6-min walk test (6MWT) and health-related quality of life (HRQoL) in older subjects. Our secondary aim was to determine the distance to be completed on the 6MWT for the subject to achieve a score of 50 on the Short Form (36) Health Survey (SF-36). Associations were tested using linear correlation and multivariate linear regression. Participants were 130 healthy older individuals. The predictive performance of the 6MWT based on an SF-36 score of 50 was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
3
14
0
1
Order By: Relevance
“…16 Observed muscle strength values overlapped considerably between the consecutive walking categories, indicating that other patient characteristics, such as sex and BMI, may affect walking performance also. 14,15,17 Concerted contraction of muscle groups as a compensation for weakness may play a role as well. 16 To compensate for weak quadriceps muscles, a hip extensor might be included for knee extensor strategy, ie, using the 2 joint characteristics of the hamstring muscle to move the knee toward extension.…”
Section: Discussionmentioning
confidence: 99%
“…16 Observed muscle strength values overlapped considerably between the consecutive walking categories, indicating that other patient characteristics, such as sex and BMI, may affect walking performance also. 14,15,17 Concerted contraction of muscle groups as a compensation for weakness may play a role as well. 16 To compensate for weak quadriceps muscles, a hip extensor might be included for knee extensor strategy, ie, using the 2 joint characteristics of the hamstring muscle to move the knee toward extension.…”
Section: Discussionmentioning
confidence: 99%
“…Applications of the simple, affordable and reproducible 6MWT have been presented in such a plethora of publications that any collection of references could by no means be considered complete. We recall a selected series of recent 6MWT-related contributions covering various medical fields [ 26 33 ], in addition to pulmonary rehabilitation highlights [ 15 , 16 , 21 , 34 37 ]. It is striking that in the overwhelming majority of those publications the linear regression tools were employed and linearized models have been used, resulting in rather high standard deviations of the involved random variables.…”
Section: Mwt Modelsmentioning
confidence: 99%
“…Therefore, a limitation of their study was that no robust conclusions on the influence of psychological factors on 6-minute walking distance could be drawn. Another study with healthy volunteers showed correlations between the 6-minute walking distance and the psychological component of quality of life [29].…”
Section: Introductionmentioning
confidence: 98%